GAYA HIDUP SELEBGRAM DENGAN ADANYA ENDORSE DI KOTA PEKANBARU - Muhammad Ulul Azmi; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Endorse is an act of supporting or supporting something. Endorse is currently trending on Instagram social media. Online shop finally uses endorse services to promote goods that will be consumed by the public. One of the problems faced today is the endorse lifestyle carried out on social media Instagram makes celebrities more and more exist in their daily lives. Through this study, researchers wanted to find out how the lifestyle with the endorse in Instagram social media in the city of Pekanbaru. This research is a qualitative descriptive study that makes individuals as research subjects. Research informants determined by purposive procedure. Data were collected using three methods, namely interviews, observation and documentation. In conducting interviews, the informants were Pekanbaru students who had 5 informants in this study. Data interpretation is done in stages starting from data collection, data reduction until conclusions and research recommendations are obtained. From the results of research that has been done that Pekanbaru sellers do endorse because of the many online shops that exist and make themselves as a means of promoting online shop products. With so many endorse products coming in, there is a difference in lifestyle between celebrities and ordinary people. This is also driven by family economic factors that support these activities. This situation also finally makes the celebrity shop no longer because of necessity but rather the value of the sign attached to the item. Therefore Pekanbaru celebrities are famous for their luxurious lifestyles. Keywords: Lifestyle, celebrity instagram, and endorse